Health and safety in exercise for special people: can disability, chronic condition and wellness coexist? (2012)
Despite the presence of a disability, special persons have the potential for health, safety and wellness to the same extent as those without disability. The near-normal lifespan of many people with disabilities and their involvement in family and community activities provide strong rationale for addressing their long-term health and wellness. This paper therefore seeks to review the question: “Can Disability, Chronic Conditions and Wellness Coexist?” The need for and importance of exercise to people with disabilities and chronic health conditions towards maintaining the highest possible levels of wellness in spite of their chronic condition and disability status are stressed. Recommendations were made for people with chronic health conditions and disabilities on the general guidelines for developing exercises and sports.